Problematika Penentuan Jujuran Di Desa Muara Sumpoi, Kecamatan Murung Kabupaten Murung Raya - Subli, Subli (IAIN Palangka Raya, 2015)
This research receipts kind of sociological research of Islamic law, or subject using purposive sampling technique that is choosing the subject of research to be the main subject in the data collection in the field. Validating the data of this study using the technique of triangulation that is comparing the observed data with the results of interviews and data analysis techniques is data collection (collecting data), data reduction (Data Reduction), a data display (presentation of data), and data conclousion (conclusion). Of the existing problems, can be obtained a description of the research that determination Problems honesty in the village of Muara Sumpoi due to the factors that influence it, and the more dominant factor is economic. How that is done to resolve the problem of determining the honesty, which gives the sense of religious customs associated with honesty. The way that is done in the view of Islam justified, that honesty should be something that does not contradict the Shari'ah of Islam, because there are no provisions in the governing religion